2015
DOI: 10.16965/ijar.2015.316
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of Gracilis Muscle and Its Vascular Pedicles

Abstract: Background: Gracilis muscle being easily accessible and functionally a weak muscle is suitable for muscle graft to replace the damaged muscle in any part of the body. The length of the muscle, vascular pedicles and limited donor site morbidity helps the surgeon to plan accordingly. The muscle receives a number of vascular pedicles ranging from one to five. The source of these pedicles varies. Material and Methods: The study was conducted on 36 formalin fixed lower limbs of both sexes of unknown age from the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Most often (63.24%), the main vascular pedicle was located at a distance of 88-112 mm from the origin of m. Gracilis. These results were approximately the same as obtained in the observations of Rajeshwari MS, Roshankumar BN [15] and Vigato E et.al. [5], in which they mentioned that their number was 1-5 (most 1-3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most often (63.24%), the main vascular pedicle was located at a distance of 88-112 mm from the origin of m. Gracilis. These results were approximately the same as obtained in the observations of Rajeshwari MS, Roshankumar BN [15] and Vigato E et.al. [5], in which they mentioned that their number was 1-5 (most 1-3).…”
Section: Discussionsupporting
confidence: 92%
“…An analysis of the literature data shows that the average width of the muscle part of m. Gracilis at its base, in the middle and at the end is 34.5±6.395, 26.3±4.682, 17.4±3.527 mm, respectively. At the same time, Dziedzic DW, et.al [8] and Rajeshwari MS, Roshankumar BN indicated the width of the belly of m. Gracilis 31.9 and 39 mm only, respectively [15].…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that the first vascular pedicle is placed at a distance of 105AE20 mm from the pubic tubercle. 15 In the present study, this distance was 93.6AE35.6 mm on the right lower extremity and left lower extremity had still proximal topography of the first pedicle. In another study, 16 it was reported that the proximal and distal pedicles of the gracilis were located 60 mm and 266 mm away from the pubic tubercle.…”
Section: Discussionsupporting
confidence: 42%
“…3 Gracilis receives pedicles ranging between one and five and 75% of the limbs have two vascular pedicles. 15 In our study, the pedicles ranged between one and three. It was reported that the first vascular pedicle is placed at a distance of 105AE20 mm from the pubic tubercle.…”
Section: Discussionmentioning
confidence: 69%
“…Length of muscle in both male &femal was more compared to others studies, muscle belly in male is more when compared to theirs studies &less in females compared tohurbanetal [9], total tendon length in both male & femal is more compared to others study, distal tendon length in both male & femal is more compared to others study, pedicle length from origin was less compared to vigatoetal [5], morrisetal [10], machii vetal [13], rajeshwarietal [14], lainetal [2] studies and more compared to Hurban etal 9 , Hussy et al [11], Dorothee etal [15]. Gracilis muscle derives its vascular supply from a wide range of arteries.…”
Section: Discussionmentioning
confidence: 76%